PENGARUH CAPITAL INTENSITY, RISIKO PERUSAHAAN, DAN KOMPENSASI RUGI FISKAL TERHADAP PENGHINDARAN PAJAK - Muhammad Ichsan Kamil (2022)
This study aims to determine the effect of capital intensity, company risk and fiscal loss compensation on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. This study is a quantitative study with secondary data consisting of 75 samples of companies collected using purposive sampling method. data analysis technique in this study uses a regression model selection test, classical assumption test of panel data regression and hypothesis testing and is processed using software STATA version 16. The results of this study indicate that (1) capital intensity has no significant effect on tax avoidance, (2) company risk has a significant positive effect on tax avoidance, (3) fiscal loss compensation has no significant effect on tax avoidance.